Optimal Placement of Vibration Control Systems in a Smart Civil Engineering Structure - Chitaoui, Houssameddine; Megnounif, Abdellatif; Benadla, Zahira (Salehan Institute of Higher Education, 2025)
Advancements in construction technologies have led to the development of lighter and more flexible structures, which pose new challenges in terms of seismic resistance. This study explores the effectiveness of integrating an Active Tendon (AT) control system to mitigate seismic-induced vibrations in tall buildings. The main objective is to identify the optimal placement of these active control devices to maximize structural performance. To this end, three optimization approaches are investigated: modal controllability analysis, controllability index evaluation, and genetic algorithm (GA)-based optimization. The methodological approach is based on the development of a comprehensive flowchart that integrates the optimization procedures alongside a comparative assessment of passive and active control strategies. Detailed simulations were carried out in MATLAB, enabling accurate time-history analyses and the implementation of customized control algorithms. This framework enables extensive parametric studies and supports a rigorous assessment of control system performance. The results clearly show that optimal tendon placement leads to a substantial improvement in vibration mitigation compared to uncontrolled cases. Comparative analyses underscore the respective strengths and applicability domains of each optimization method, confirming their effectiveness in identifying optimal actuator locations. The novelty of this study lies in the integration of modal and evolutionary optimization techniques within a unified framework, offering a systematic and versatile approach to the placement of control systems in civil engineering structures. The practical recommendations derived from this study provide valuable guidance for engineers and designers seeking to improve structural performance under seismic loading.